ABOUT THE ESTIMATION PROCEDURE OF TRAINING LEVEL IN PHYSICS AT TECHNICAL UNIVERSITY - Alexander F. An; Vladimir M. Sokolov (Высшее образование в России)
The article presents a possible approach to designing the evaluation procedures, for determination of the successfulness of learning professionally oriented physics course attechnical university. The authors introduce the concept “physical competency” characterizing student’s preparedness to solve successfully professional tasks basing on physical laws, models and effects. There are marked out the main constituents of physical competency, which can be viewed as estimated learning outcomes. The authors suggest using the typical tasks implemented in professional cycle of disciplines for evaluation students’ learning level and physical competence level. The selected empirical data of technical students’ examinationshow that the learning level in physics is rather low and that the professional disciplines do notpromote adequately to the development of their physical competency.